The New Public Health Workforce: Employment Outcomes of Public Health Graduate Students. Issue 1 (January 2021) - Krasna, Heather; Kornfeld, Julie; Cushman, Linda; Ni, Shuyue; Antoniou, Pantelis; March, Dana
Abstract : Context: Much has been written about the public health workforce, but very little research has been published—and none in a peer-reviewed journal or other report since 1992—regarding the employment outcomes and employment sectors of graduate students pursuing public health as an area of study. Objectives: Our objectives were to review the literature and analyze data regarding the employment outcomes of public health graduate students and to examine how public health schools and programs might respond to changes in the sectors hiring their graduates. Design: We reviewed the literature regarding the employment of public health graduates; analyzed 5 years of graduate outcomes from Columbia University's Mailman School of Public Health using logistic regression; and we examined data collected by the Association of Schools & Programs of Public Health. Participants: The study included data from surveys of 2904 graduates of Columbia University's Mailman School of Public Health, across 5 graduating cohort years, for whom there were employment sector data available for 1932. Results: Much of the research on the public health workforce has defined it as governmental public health. Across each of 5 graduating classes from Columbia University's Mailman School of Public Health, the odds of for-profit sector employment increased by 23% (2012-2016), while hiring by government agencies declined or remained flat. Publicly available employment data from the Web sites of schools of public health and from surveys by the Association of Schools & Programs of Public Health show that hiring of new graduates by for-profit corporations now either closely matches or exceeds governmental hiring at many schools of public health. Conclusions: Public health graduates are increasingly working outside of government, and additional analyses are required to determine whether core competencies of public health curricula reflect the needs of the employers that are hiring public health graduates today. Schools and programs of public health should invest in their career services offices and gather input from employers that are currently hiring their graduates, especially as the sectors hiring them may be changing.